2019
DOI: 10.1177/1533033819887962
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA BANCR Promotes Pancreatic Cancer Tumorigenesis via Modulating MiR-195-5p/Wnt/β-Catenin Signaling Pathway

Abstract: Long noncoding BRAF-activated noncoding RNA has been reported to be tightly associated with tumorigenesis and development in various types of cancers. However, the expression, biological function, and modulatory mechanism of BRAF-activated noncoding RNA in pancreatic cancer remained unclear. In the present work, we explored the carcinogenic activity and underlying mechanism of BRAF-activated noncoding RNA on pancreatic cancer in vitro. We identified that BRAF-activated noncoding RNA was upregulated in pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 54 publications
(60 reference statements)
0
32
0
Order By: Relevance
“…31 Wu et al demonstrated that BRAF-activated noncoding RNA promotes tumorigenesis of pancreatic cancer by sponging miR-195. 32 Overall, our results demonstrated that SNHG12 could accelerate tumorigenesis of DLBCL cells through miR-195 sponging.…”
Section: Discussionmentioning
confidence: 57%
“…31 Wu et al demonstrated that BRAF-activated noncoding RNA promotes tumorigenesis of pancreatic cancer by sponging miR-195. 32 Overall, our results demonstrated that SNHG12 could accelerate tumorigenesis of DLBCL cells through miR-195 sponging.…”
Section: Discussionmentioning
confidence: 57%
“…The function of the Wnt/β-catenin pathway on EC growth had been well-established (18). β-Catenin maintains epithelial cell integrity, an important barrier for blocking tumor metastasis (19). Additionally, hypophosphorylated β-catenin transfers into the nucleus and binds to transcription factors, leading to transcriptional activation of specific target genes, including Cyclin D1, C-MYC, and MMP-7, all of which contribute to cell survival, cell cycle, uncontrolled proliferation, and distant metastasis (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, treatments limited to chemotherapy associated with resistance development do not re ect well on patients who defy surgical resection, carrying with primary migration, or diseases with high recurrence [29]. Accumulating researches have shown that lncRNA is an essential cell regulator in tumor progression, including osteosarcoma, which brings new ideas for the treatment of osteosarcoma [30][31][32]. This study rst explored a new lncRNA, namely LINC00485.…”
Section: Discussionmentioning
confidence: 99%